Effects of curcumin on synapses in APPswe/PS1dE9 mice. (June 2016) - He, Yingkun; Wang, Pengwen; Wei, Peng; Feng, Huili; Ren, Ying; Yang, Jinduo; Rao, Yingxue; Shi, Jing; Tian, Jinzhou
Significant losses of synapses have been demonstrated in studies of Alzheimer's disease (AD), but structural and functional changes in synapses that depend on alterations of the postsynaptic density (PSD) area occur prior to synaptic loss and play a crucial role in the pathology of AD. Evidence suggests that curcumin can ameliorate the learning and memory deficits of AD. To investigate the effects of curcumin on synapses, APPswe/PS1dE9 double transgenic mice (an AD model) were used, and the ultra-structures of synapses and synapse-associated proteins were observed. Six months after administration, few abnormal synapses were observed upon electron microscopy in the hippocampal CA1 areas of the APPswe/PS1dE9 double transgenic mice. The treatment of the mice with curcumin resulted in improvements in the quantity and structure of the synapses. Immunohistochemistry and western blot analyses revealed that the expressions of PSD95 and Shank1 were reduced in the hippocampal CA1 areas of the APPswe/PS1dE9 double transgenic mice, but curcumin treatment increased the expressions of these proteins. Our findings suggest that curcumin improved the structure and function of the synapses by regulating the synapse-related proteins PSD95 and Shank1.